2018
DOI: 10.1021/acs.jpcc.8b02462
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Atomic Force Microscopy and Electrochemical Quartz Crystal Microbalance Studies on the Electrodeposition and Oxidation of Silicon

Abstract: In this paper, we investigated how the anion of an ionic liquid (IL) affects nanostructure of electrode/electrolyte interface and subsequently the deposition process of silicon. For this purpose, ILs with the same cation 1-butyl-1-methylpyrrolidinium and various anions, namely, tris­(pentafluoroethyl) trifluorophosphate ([Py1,4]­FAP), bis­(trifluoromethylsulfonyl)­amide ([Py1,4]­TFSA), and bis­(fluorosulfonyl)­amide ([Py1,4]­FSA) were chosen. Cyclic voltammetry and electrochemical quartz crystal microbalance (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Considering primary applications, silicon-based batteries from scrap material could be a decent option to replace primary Zn-air batteries in the future, given the excellently flat and long-lasting discharge characteristics of silicon in comparison to zinc. Furthermore, similar to Ca-O 2 batteries, it does not appear ultimately impossible to tackle the missing rechargeability of Si-air batteries [106,107,108], which is effected by thermodynamics and exemplarily explained with the help of polarization curves in comparison to rechargeable Fe-air batteries in Figure 6.…”
Section: Introductionmentioning
confidence: 99%
“…Considering primary applications, silicon-based batteries from scrap material could be a decent option to replace primary Zn-air batteries in the future, given the excellently flat and long-lasting discharge characteristics of silicon in comparison to zinc. Furthermore, similar to Ca-O 2 batteries, it does not appear ultimately impossible to tackle the missing rechargeability of Si-air batteries [106,107,108], which is effected by thermodynamics and exemplarily explained with the help of polarization curves in comparison to rechargeable Fe-air batteries in Figure 6.…”
Section: Introductionmentioning
confidence: 99%
“…Considering primary applications, silicon-based batteries from scrap material could be a decent option to replace primary Zn-air batteries in the future, given the excellently flat and long-lasting discharge characteristics of silicon in comparison to zinc. Furthermore, similar to Ca-O2 batteries, it does not appear ultimately impossible to tackle the missing rechargeability of Si-air batteries [106][107][108], which is effected by thermodynamics and exemplarily explained with the help of polarization curves in comparison to rechargeable Fe-air batteries in Figure 6. Based on thermodynamic considerations, the currently missing reversibility of Si-air batteries compared to other metal-air systems arises from two major issues.…”
Section: Electrochemical Performance Of Metal-air Batteriesmentioning
confidence: 99%
“…While the equilibrium potential of silicon in EMIm(HF)2.3F lies well within the stability window of the electrolyte, the RTIL might easily decompose upon recharge, if the reduction potential is shifted to critically low values. The electrochemical deposition of Si in other RTILs have already been reported [106][107][108], which might enable the rechargeability of Si also on a battery level in near future.…”
Section: Electrochemical Performance Of Metal-air Batteriesmentioning
confidence: 99%
“…As only ions are present in ionic liquids, by changing the anions of the ionic liquids, the speciation of metals/semiconductor ions can be altered (Borisenko et al, 2018; Lahiri et al, 2018a). A change in the speciation leads to a different electrochemical behavior and has also shown to affect the morphology of the deposit (Pulletikurthi et al, 2013, 2014; Borisenko et al, 2018; Lahiri et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…As only ions are present in ionic liquids, by changing the anions of the ionic liquids, the speciation of metals/semiconductor ions can be altered (Borisenko et al, 2018; Lahiri et al, 2018a). A change in the speciation leads to a different electrochemical behavior and has also shown to affect the morphology of the deposit (Pulletikurthi et al, 2013, 2014; Borisenko et al, 2018; Lahiri et al, 2018a). Interestingly, it was reported that changing the cations of the ionic liquids also affects the morphology of the electrodeposits (Zein El Abedin et al, 2006; Al-Salman and Endres, 2009; Ispas et al, 2010).…”
Section: Introductionmentioning
confidence: 99%